Phytochemicals and Biological Activities of Musa paradisiaca cv. Sekaki Florets - Khong, Heng Yen; Boonpisuttinantant, Korawinwich; Ariffin, Muhammad Mirza (Pharmaceutical Research: Recent Advances and Trends Vol. 10, 2024)
Previous findings on Musa paradisiaca have demonstrated diverse chemical compositions and their potential applications in various fields, ranging from pharmaceuticals to industrial uses. Several studies have explored the potential of its florets as a source of beneficial compounds and phytochemicals. In this study, different solvent extracts of M. paradisiaca florets were evaluated for their total phenolic content, with the ethyl acetate fraction showing the highest phenolic content at 481.53 mg GAE/g. The extracts were also analysed for flavonoid content, antioxidant activities, antimicrobial properties, and cytotoxicity. The ethyl acetate extract exhibited the best ability to scavenge 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radicals among all the tested fractions. A positive linear correlation was established between the phenolic content of the extracts and their antioxidant capacity. Furthermore, the extracts demonstrated significant antimicrobial activity against all tested Gram-positive and Gram-negative bacteria, with minimum inhibitory concentrations (MIC) and minimum bactericidal concentrations (MBC) ranging from 450 µg/mL to as low as 14.07 µg/mL. The cytotoxicity of the extract, determined through the MTT assay against cancerous cell lines DU-145 (human prostate cancer cell lines) and HeLa (human cervical cancer cell lines), was comparable to that of chemotherapeutic drugs such as doxorubicin hydrochloride, cisplatin, and fluorouracil. The IC50 values for the extract against DU-145 and HeLa cells were 0.8925 µM/mL and 0.9152 µM/mL, respectively. These results indicate that M. paradisiaca florets have substantial potential for development into pharmaceutical products capable of inhibiting cellular damage caused by free radicals.